Evaluation of Demographic and Clinical Characteristics of Drug Intake and Suicide Attempt in Adolescents - Funda Kurt; Burcu Akbaba; Halil İbrahim Yakut; Emine Dibek Mısırlıoğlu (Galenos Yayinevi, 2020)
Introduction:Suicide attempts by overdose drug intake are important public health problems in adolescents. The aim of this study was to evaluate the demographic and clinical characteristics of the patients with suicide attempts.Methods:Adolescents, who were admitted to our pediatric emergency department with suicide attempt between January 1, 2014 and December 31, 2018, were evaluated retrospectively.Results:The median age of 784 patients included in the study was 190 months and 662 (84.4%) of them were female. It was determined that 429 (54.7%) of the cases were taking multiple drugs. Analgesic drug intake (non-steroidal anti-inflammatory and paracetamol) was the most common (47.1%), antidepressant (22.6%) and common cold drugs (18.0%) were second and third respectively. One hundred-three (13.1%) of the cases were in early adolescence (9-13 years), 533 (68.0%) were in middle adolescence (14-16 years), 148 of them were in late adolescence (17-19 years). Of our patients, 201 (25.6%) had pediatric psychiatry follow-up and 154 (19.6%) were taking regular medication. It was determined that 185 (23.6%) of the cases had two or more suicides attempts. The most common symptoms were detected as gastrointestinal (60.3%) and neurological (42.6%) symptoms. Seven hundred-forty two (94.6%) of the cases were hospitalized [380 (51.2%) in emergency observation, 188 (25.3%) in intensive care unit, 174 (23.5%) in pediatric ward]. It was found that 3 (0.4%) patients who died were female and it was their first suicide attempts and they were taking single drug (amphetamine, antidepressant and angiotensin-II antagonist).Conclusion:Suicidal drug intoxications are more common in middle adolescence and girls. Multiple drugs and especially accessible nonprescription drugs are poisoning agents. Multidisciplinary follow-up is important for the risk of recurrence of suicide attempts.